Monitoring of BLAD, DUMPS, CVM, BC and FXID in Turkish Native Cattle Breeds - Hasan Meydan (Journal of Agricultural Sciences)
In this study, Turkish native cattle breeds were monitored with respect to the genetic disorders defined as bovine leukocyte adhesion deficiency (BLAD), deficiency of uridine monophosphate synthase (DUMPS), complex vertebral malformation (CVM), bovine citrullinaemia (BC) and factor XI deficiency (FXID). All these are autosomal recessive hereditary disorders causing serious economic losses in dairy cattle breeding throughout the world. In order to determine the presence or the absence of BLAD, DUMPS, CVM, BC and FXID genotypes in native cattle breeds, 200 heads of Anatolian Black, 100 heads of East Anatolian Red, 100 heads of Turkish Grey, 50 heads of Anatolian Southern Yellow, 50 heads of South Anatolian Red and 9 heads of Zavot breed (totally 509 heads) were sampled. Genomic DNA was obtained from blood and the amplicons were obtained by using PCR. PCR products were digested with TaqI, AvaI, EcoT22I and AvaII restriction enzymes for BLAD, DUMPS, CVM, and BC, respectively. Digested products of BLAD, DUMPS CVM and BC were analyzed by agarose gel electrophoresis. PCR products of FXID were analyzed by only agarose gel electrophoresis stained with ethidium bromide. The results demonstrated that no animals examined were the carrier of these genetic disorders. Thus, it can be concluded that mutant alleles of BLAD, DUMPS, CVM, BC and FXID are absent in Turkish native cattle breeds.